937 COMMUNITY ORIENTATION AND HYBRID PHYSICIANS IN AMBULATORY EMERGENCY CARE FOR OLDER PEOPLE. (14th June 2022) - Glogowska, M; Lasserson, D; Reeve, J
Abstract: Introduction: AEC (Ambulatory Emergency Care) provides acute assessment and treatment in the community for acutely unwell complex older patients, with patients staying in their own homes overnight. This investigation aimed to understand the impact of the AEC Setting on Clinical Decision-Making. Method: Three AEC sites were purposively sampled to recruit twelve clinicians with backgrounds in Geriatrics, General Practice, Emergency and Acute Medicine. This qualitative investigation used focused ethnography within a case study approach to understand the decision-making processes in the context of the AEC environment. Observation during an AEC shift was complemented by informant interviews. A framework approach to thematic analysis used 'a priori' and data derived codes to develop explanatory themes. Constant comparison and cognitive task analysis were used to evaluate the clinicians' decision-making processes for index patient cases. Results: Across-case analysis of the experience and training of the AEC clinicians identified that the main similarity in training was having a varied background experience. These 'hybrid physicians' were able to work across professional boundaries and considered their diversity of training a strength. The AEC clinicians had considerable contextual awareness of their environment and how this differed from their routine clinical practice. The participants felt that AEC working altered their thresholds for concern and increased their community orientation. Conclusion: This critical example demonstrates the importance of diversity of background training and community orientation when considering alternatives to acute hospitalisation for unwell older adults. As more interventions such as the Urgent Community Response are implemented across the UK, further training is needed to ensure that AEC clinicians obtain a broad spectrum of practice. Future research is needed to investigate optimal team and skill mix in AEC.